OPTIMIZATION OF TREATMENT STRATEGIES FOR ACUTE CORONARY SYNDROME PATIENTS WITH ARRHYTHMIC COMPLICATIONS - Malikova Dildora Maxsud qizi,; Sharopova Nargiza Samiyevna, (TADQIQOTLAR, 2025)
Abstract.  The  presence  of  acute  heart  failure  in  patients  with  myocardial infarction  remains  one  of  the  current  problems  in  cardiology.  The  urgency  of  the problem is determined by the frequency of complications resulting from this pathology and the lack of a sufficiently effective treatment.